Seasonal Partitioning of Rainfall in Second-Growth Evergreen Temperate Rainforests in Chiloé Island, Southern Chile - Frêne, Cristián; Núñez-Ávila, Mariela; Castro, Ben; Armesto, Juan J. (Frontiers in Forests and Global Change, 2022)
Rainfall partitioning in secondary forests from southern Chile is relevant in the climate change scenario, in which a 30% reduction in summer precipitation has been projected for the temperate region. Logging and degradation of old-growth forests has resulted in extensive secondary forests, over large areas of the Chiloé Archipelago as well as the mainland. These secondary forests are simple tree communities, dominated by two broad-leaved tree species, evergreen Drimys winteri and Nothofagus nitida, and have the potential to provide multiple benefits to society, including water provision, soil protection, and wood-derived products. Here, we ask how southern South American secondary rainforests modulate rainwater redistribution considering precipitation partitioning. We evaluated the seasonality of throughfall and stemflow components of precipitation, to assess ecohydrological processes for water regulation in a climate change context, where summer droughts have been more frequent in the last decade. The partitioning of gross rainfall (TP) into throughfall (TH), stemflow (ST), and canopy interception (IN) in relation to forest structure, was assessed in four forest plots (400 m² each) in Senda Darwin Biological Station, Chiloé. TH and ST were measured seasonally for 35 rainfall events from 2019 to 2021. IN water losses were estimated from the mass balance equation. Results indicate that the secondary rainforest intercepts 33% of TP (990 mm of the total monitored), where 59% of the volume corresponds to TH and 7% to ST, which taken together account for nearly 100% the rainwater that reaches the forest floor. Canopy IN varied seasonally from 25 to 40% of total rainfall, with maximum values occurring in the growing season (spring-summer). We found no statistical relation between ST and forest structural parameters (DBH, Basal Area). We explored the contribution of the two dominant tree species to ST and discuss the results in a climate change context. Finally, we propose to incorporate this hydrologic knowledge into adaptive forest management strategies to maximize ecosystem benefits to people. If these ecosystems were properly managed, they have the potential to provide multiple benefits to society within this century, such as water provision and soil protection in addition to carbon sequestration in biomass.